(untitled) (Global Journal of Science Frontier Research, 2019)
Soil is an important natural resource for growing plants and the suitability of soil for crop production is based on the quality of the soil’s physical, chemical and biological properties. The objectives of the study were to determine the soil physical and chemical properties and characterize the spatial variability of soil physico-chemical properties across the study area. The study was conducted at Crop, Soil and Pest Management Research Farm, Futa. Soil samples were collected from six sampling depths between 0-60 cm at an interval of 10 cm at different 20 points across the field while coordinates of the soil sampling points were determined using Global Positioning System (GPS) procedures. The test for variance was carried out on physical properties of %sand, %silt, %clay, bulk density (g/cm 3 ), %porosity, %water holding capacity (WHC) and soil hydraulic conductivity and chemical properties on pH, organic matter content (%), total nitrogen (%), available phosphorus (ppm), calcium, magnesium, sodium and potassium (cmol/kg), and effective cation exchange capacity (cmol/kg).